COX‐2‐10aa‐PGIS Gene Therapy Improves Erectile Function in Rats after Cavernous Nerve Injury. (3rd April 2013) - Lin, Haocheng; Yuan, Jiuhong; Ruan, Ke‐He; Yang, Wenli; Zhang, Junlan; Dai, Yutian; Wang, Run
Abstract: Introduction: Erectile dysfunction (ED) is a very common complication after radical prostatectomy. COX‐2‐10aa‐PGIS is a newly engineered protein with COX‐2 and prostacyclin synthase activities that converts arachidonic acid directly to prostacyclin (prostaglandin I2 [PGI2]). PGI2 is a potent smooth muscle relaxant. Aim: The purpose of this study was to explore the effect and mechanism of COX‐2‐10aa‐PGIS gene therapy in penile rehabilitation. Methods: Bilateral cavernous nerve crush (BCNC) in adult Sprague‐Dawley rats was used to mimic radical prostatectomy‐induced ED. Sprague‐Dawley rats were randomly assigned into four groups: 1. sham surgery; 2. BCNC; 3. BCNC + null control recombinant adenovirus intracavernous injection; and 4. BCNC + Ad‐COX2‐10aa‐PGIS intracavernous injection. Twenty‐eight days later, intracavernosal pressure (ICP) was recorded under cavernous nerve stimulation; in the meantime, the mean arterial pressure (MAP) was monitored. At the end of the measurement, the penis was harvested and processed for (i) immunohistochemistry analysis of endothelial nitric oxide synthase (eNOS), alpha‐smooth muscle actin (α‐SMA), and transforming growth factor beta‐1 (TGF‐β1); (ii) Masson's trichrome stain for smooth muscle/collagen ratios; (iii) Western blot of eNOS, α‐SMA, TGF‐β1, and COX2‐10aa‐PGIS; and (iv) terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay for apoptosis. Main Outcome Measures: Erectile function was evaluated by ICP/MAP. Smooth muscle and endothelium functions in corpora cavernosum were assessed by Masson's trichrome stain, immunohistochemistry, and Western blot. Apoptosis was identified by TUNEL assay. Results: The results were the following: 1. COX2‐10aa‐PGIS gene therapy improved erectile function (82%, compared with control) in the BCNC rat model; 2. COX2‐10aa‐PGIS gene therapy increased eNOS (121%) and α‐SMA (118%) expression and decreased TGF‐β1 (45%) expression; 3. COX2‐10aa‐PGIS gene therapy reduced cell apoptosis after cavernous nerve injury (64%); and 4. COX2‐10aa‐PGIS gene therapy improved smooth muscle/collagen ratios (81%). Conclusion: Our data demonstrated that COX2‐10aa‐PGIS improved erectile function after cavernous nerve injury through antifibrotic and anti‐apoptotic mechanisms.